Risk Factors for the Occurrence of Scalp Hematoma in Term Neonates in King Chulalongkorn Memorial Hospital - Chaiyawut Paiboonborirak; Surasith Chaithongwongwatthana; Yada Kunpalin; Anongnart Sirisabya (The Royal Thai College of Obstetricians and Gynaecologists, 2018)
Objectives: To determine the incidence and associated factors of neonatal scalp hematoma.Materials and Methods: This prospective case-control study included all term singleton live newborns that delivered in King Chulalongkorn Memorial Hospital during July 2016 to October 2016. All neonates were prospectively evaluated and divided into two groups: cases with scalp hematoma and controls. Diagnoses of neonatal scalp hematoma either cephalhematoma or subgaleal hemorrhage were confirmed by the experienced neonatologist. Medical records of these neonates and their mothers were reviewed to collect demographic data and information regarding their processes of labor and delivery. Logistic regression analysis was used to identify the risk factors associated with presence of neonatal scalp hematoma.Results: A total of 938 term neonates were included in this study. The incidence of neonatal scalp hematoma was 3.19% (30/938). Operative obstetrics (vacuum and forceps extraction) were found to have the highest rate (15.38%) of scalp hematoma when compare with other routes of delivery. Factors associated with neonatal scalp hematoma were primiparity (adjusted OR 4.86, 95% CI 1.61-14.58) and prolonged second stage of labor (adjusted OR 4.31, 95% CI 1.08-17.25). When analysis was done in only vaginally delivered neonates, the significant factors were primiparity (adjusted OR 3.84, 95% CI 1.26-11.71) and artificial rupture of membranes (adjusted OR 2.93, 95% CI 1.24-6.97).Conclusion: Neonatal scalp hematoma was common. Primiparous women significantly increased risk of neonatal scalp hematoma regardless of route of delivery.